ANALISIS KAUSALITAS KEMISKINAN, PEKERJA ANAK DAN PUTUS SEKOLAH DI INDONESIA - Selvia, Sri; Yeniwati, Yeniwati (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This study was conducted to determine and analyze the relationship between poverty variables, child labor and dropout rates in Indonesia and how the response of a variable due to the shock of other variables. This type of research is descriptive and associative research, with the data used are secondary data types, namely panel data from 33 provinces in Indonesia from 2010 to 2018 with data collection techniques documentation and literature studies obtained from related institutions and institutions namely the Central Statistics Agency and the Ministry of Women's Empowerment and Child Protection. Analysis of the data used in this research is descriptive analysis and inductive analysis. In the inductive analysis there are several tests that must be performed, namely: (1) Unit root test, (2) Determination of Optimum Lag, (3) Stability Test, (4) Granger Causality Test, (5) Cointegration Test, (6) PVAR Test , (7) IRF test and (8) VD testThe results in this study explain that (1) poverty and child labor do not have a causality relationship only has a one-way relationship while poverty and drop out have a causality relationship. Furthermore, child labor and dropout rates have a causal relationship. The FEVD analysis explains that (4) In the short term child labor and dropout rates do not contribute to influencing the movement of poverty in Indonesia while in the long run child labor shocks and dropout rates affect the variability of poverty in Indonesia. (5) In the short term the variability of child labor is only affected by poverty while in the long run poverty shocks and dropout rates affect the movement of child labor in Indonesia. (6) variability in the number of dropouts in the short and long term is influenced by poverty shocks and dropout rates.